CMake Best Practices : Discover Proven Techniques for Creating and Maintaining Programming Projects with CMake - Berner, Dominik (Packt Publishing, Limited, 2022)
Explore a compendium of tips, tricks, and techniques for leveraging CMake and empowering your software development workflow. Key Features Understand what CMake is, how it works, and how to interact with it Discover how to properly create and maintain well-structured CMake projects Explore tools and techniques to get the most out of your CMake project Book Description CMake is a powerful tool used to perform a wide variety of tasks, so finding a good starting point for learning CMake is difficult. This book cuts to the core and covers the most common tasks that can be accomplished with CMake without taking an academic approach. While the CMake documentation is comprehensive, it is often hard to find good examples of how things fit together, especially since there are lots of dirty hacks and obsolete solutions available on the internet. This book focuses on helping you to tie things together and create clean and maintainable projects with CMake. You'll not only get to grips with the basics but also work through real-world examples of structuring large and complex maintainable projects and creating builds that run in any programming environment. You'll understand the steps to integrate and automate various tools for improving the overall software quality, such as testing frameworks, fuzzers, and automatic generation of documentation. And since writing code is only half of the work, the book also guides you in creating installers and packaging and distributing your software. All this is tailored to modern development workflows that make heavy use of CI/CD infrastructure. By the end of this CMake book, you'll be able to set up and maintain complex software projects using CMake in the best way possible. What you will learn Get to grips with architecting a well-structured CMake project Modularize and reuse CMake code across projects Integrate various tools for static analysis, linting, formatting, and documentation into a CMake project Get hands-on with performing cross-platform builds Discover how you can easily use different toolchains with CMake Get started with crafting a well-defined and portable build environment for your project Who this book is for This book is for software engineers and build system maintainers working with C or C++ on a regular basis and trying to use CMake to better effect for their everyday tasks. Basic C++ and general programming knowledge will help you to better understand the examples covered in the book.